2000
DOI: 10.1074/jbc.m003174200
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus Vulgaris Antibody Identifies Pemphaxin

Abstract: Because pemphigus vulgaris (PV) IgGs adsorbed on the rDsg3-Ig-His baculoprotein induced blisters in neonatal mice, it was proposed that anti-desmoglein 3 (Dsg 3) autoantibody causes PV. However, we found that rDsg3-Ig-His absorbs autoantibodies to different antigens, including a non-Dsg 3 keratinocyte protein of 130 kDa. This prompted our search for novel targets of PV autoimmunity. The PV IgG eluted from a 75-kDa keratinocyte protein band both stained epidermis in a pemphigus-like pattern and induced acanthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(37 citation statements)
references
References 79 publications
2
35
0
Order By: Relevance
“…Our previous studies (45) demonstrated that although adsorption of a single type of pathogenic antibody eliminates the acantholytic activity of PVIgG, this autoantibody alone is not sufficient to induce acantholysis and skin blisters. However, adding it back to the preabsorbed PVIgG restores acantholytic activity of the latter (45). Thus, the pool of disease-causing PVIgG contains autoantibodies to a group of keratinocyte self-antigens, and it is the a synergistic action of these autoantibodies that breaks up the integrity of live epidermis and induces skin blistering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies (45) demonstrated that although adsorption of a single type of pathogenic antibody eliminates the acantholytic activity of PVIgG, this autoantibody alone is not sufficient to induce acantholysis and skin blisters. However, adding it back to the preabsorbed PVIgG restores acantholytic activity of the latter (45). Thus, the pool of disease-causing PVIgG contains autoantibodies to a group of keratinocyte self-antigens, and it is the a synergistic action of these autoantibodies that breaks up the integrity of live epidermis and induces skin blistering.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of cell entry of antimitochondrial antibodies in PV may involve their binding to annexins at the keratinocyte plasma membrane (45,64). Annexins can relocate to the cytosol (65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…rPX-His specifically bound [ 3 H]ACh as well as nicotinic and muscarinic drugs, suggesting that PX is one of the KC AChR with dual, muscarinic and nicotinic, pharmacology known to be targeted by disease-causing Pab. Preabsorption of PV sera with rPX-His eliminated acantholytic activity, and eluted antibody immunoprecipitated native PX [31]. Although this antibody alone did not cause skin blisters in vivo, its addition to the preabsorbed PV IgG fraction restored acantholytic activity, indicating that acantholysis in PV results from synergistic action of autoantibodies to different self-antigens, including both AChR and desmosomal cadherins.…”
Section: Pab Identify Pemphaxin – a Novel Kc Annexin-like Molecule Bimentioning
confidence: 99%
“…The PV IgG eluted from a 75-kD KC protein band both stained epidermis in a pemphigus-like pattern and induced acantholysis in KC monolayers [31]. Screening of a keratinocyte λgt11 cDNA library with this antibody identified clones carrying cDNA inserts encoding a novel molecule that we named pemphaxin (PX) because it exhibits ∼40% similarity with annexin 2.…”
Section: Pab Identify Pemphaxin – a Novel Kc Annexin-like Molecule Bimentioning
confidence: 99%
“…The cells were isolated from the epidermis and grown in 75-cm 2 flasks (Corning Glass) at 37°C in serumfree keratinocyte growth medium (KGM) containing 0.09 mM Ca 2ϩ in a humid 5% CO 2 incubator, as detailed elsewhere (59). On the day of the experiment, ϳ80% confluent second passage cultures derived from three different donors were washed and fed with fresh KGM containing either 1 mg/ml PV IgG, 1 mg/ml normal IgG, 0.25 mM MP, 1 mg/ml PV IgG after 2 h of pretreatment with 0.25 mM MP or no additions (control), and incubated for 8 h at 37°C in a humid 5% CO 2 incubator.…”
Section: Pemphigus and Control Igg Fractions-mentioning
confidence: 99%